Advances in business and management forecasting. Vol. 11 - Lawrence, Kenneth D.; Klimberg, Ronald K. (Bingley, U.K. : Emerald, 2016)
Advances in Business and Management Forecasting presents state-of-the-art studies in the application of forecasting methodologies to such areas as finance, economics, technology, and forecasting accuracy. Volume 11 is split into four sections which address Forecasting in Marketing and Sales, Forecasting in Health Care, Forecasting in Business and Economics, and Topics in Forecasting. A number of topics are examined including brand experience, hospital bed management, population growth and online information sharing.
Optimizing resources to better forecast future profits / Kathleen Campbell Garwood, Alicia Graziosi Strandberg, Nicolle Clements -- Brand experience and customer equity prediction / Arthur Cheng-Hsui Chen, Shaw Chen, Chien-Lin Ma -- A comparative evaluation of intermittent demand forecasting with updated smoothing constants / Matthew Lindsey, Robert Pavur -- Forecasting pain and discomfort for canines with disease for establishing appropriate medication levels / Virginia Miori, Zhenpeng Miao, Yingdao Qu -- Honing a predictive model to accurately forecast the number of bed days needed to cover patient volume for a large hospital system / Alan Olinsky, Kristin Kennedy, Michael Salzillo -- Can rationality of USDAs fixed-event crop forecasts be improved? / Ran Xie, Olga Isengildina-Massa, Julia Sharp -- Business school forecasting for the real world / John Kros, William Rowe -- Forecasting the operating income of MetLife / Kenneth Lawrence, Gary Kleinman, Sheila Lawrence -- Forecasting the population growth in China based on the welfare efficiency and demographic statistics / Feng Yang, Yuan Yang, Zhimin Huang -- Modeling Los Angeles water leaks using different measures of temperature / Daniel OLeary -- How information spreads in online social networks / Christopher Quinn, Matthew Quinn, Alan Olinsky, John Quinn -- Is there a home run derby curse? / Daniel O'Leary.
Includes bibliographical references.
Print version record
Keywords: Business & Economics -- Management Science; Business & Economics -- Decision-Making & Problem Solving; Management decision making; Management & management techniques; Business & management; Business forecasting